Beyond Literal Understanding: “Womb Theft” as Metonym – An Interpretation of the Language Used to Describe Caesarean Kidnappings - Mswela, Maureen (Obiter, 2020)
The author’s attention has, in recent years, been drawn to an article with the headline, “Womb theft accused testifies”, and to another titled “Sentence reduced for attempted womb theft”. Both articles referred to “womb theft” as the appropriation of a fetus from an expectant woman by a female perpetrator who fakes a pregnancy, and then brutally kills the pregnant woman in order to appropriate the unborn child to keep as her own. Such criminals literally slash open an expectant woman’s womb to reach for the fetus in what can be described as a bizarre replication of a Caesarean section procedure. The author was not entirely clear on what writers meant by “womb theft”, which, defined literally, indicates that the object of theft is the womb/uterus and not a fetus/newborn. If a womb in its literal sense qualifies to be an object of theft, a writer could surely foresee the confusion that would follow headlines such as “Sentence reduced for attempted womb theft” or “Womb theft accused testifies.” The failure to do so exposes a conceptual skew in the discursive construction of the nature of the crime. There has been little research into problems in the language used to describe Caesarean kidnappings from the standpoint of those interested in improving legal language construction. Perhaps a special category of figurative language is required to explain how “womb theft” is used and understood here. The author pursues this task through metonymic analysis, a method that has found little application in legal theory in the South African context. The author argues that figurative expressions are repeatedly used without critical reflection, thereby confusing the recipient and obscuring communication rather than enlightening it. The author does not argue that the use of metonym in legal contexts should be eradicated since, in some instances, they enhance the understanding of legal concepts; instead, legal scholars must see through figurative language, and develop critical dialogue on the stylistic use of metonym and in so doing, master the art of legal communication.